Renal Lipidosis in Horses and Donkeys: 25 Cases (2008–2022) - Kali Slavik; Susan Bender; Leslie Sharkey; Rose Nolen‐Walston (Journal of Veterinary Internal Medicine)
ABSTRACT Background Renal lipidosis is a well‐documented histologic finding in humans and small animals with renal and metabolic disorders, but it is not well described in equids. Objective To describe the signalment, clinicopathologic indices, and postmortem findings of equids with a histologic diagnosis of both hepatic and renal lipidosis (HL + RL) and compare them to cases with hepatic lipidosis only (HL). Animals Equids with necropsy findings of renal or hepatic lipidosis (state diagnostic lab) between 2008 and 2022. Methods Retrospective case–control study. Signalment, history, necropsy diagnosis, and selected biochemical data at admission were extracted from medical records. Each case of HL + RL was assigned a matched case from group HL for comparison of clinical data. Results Renal lipidosis was diagnosed in 0.5% (25/4680) of equid necropsies. Donkeys (7/13) and pony/miniature horses (13/37) with hepatic lipidosis were more likely to also have renal lipidosis compared to horses (5/141; p = 0.0006, RR = 15.1and p < 0.0001, RR = 9.9, respectively). No cases of renal lipidosis were identified without concurrent hepatic lipidosis. The predominant presenting complaints involved gastrointestinal (16/25) and neurologic (12/25) systems. Compared to group HL, group HL + RL had significantly higher admission plasma lactate concentration (+6.2 mmol/L, 95% CI 0.04–13.1, p = 0.04) and GGT activity (+246 U/L, 95% CI −480.4–1870, p = 0.02). No significant differences were detected in creatinine or triglyceride concentrations. Conclusions Renal lipidosis is an occasional postmortem finding in equids with hepatic lipidosis and is more common in donkeys, ponies, and miniature horses compared to horses. The clinical implications of renal lipidosis remain unclear.